2015
DOI: 10.17265/1537-1514/2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Level of the Financial Inclusion in the African Countries and in the World Group Regions

Abstract: One key component of inclusive development is financial inclusion, an area in which Africa has been lagging behind unlike other continents. At most, one adult out of four in Africa has access to an account in a formal financial institution. The objective of this study is to find out the level of the financial inclusion among 41 African countries on one hand and the level of the financial inclusion among the world six group regions on the other hand. To find out which country or which group region has a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 3 publications
1
12
0
2
Order By: Relevance
“…Five variables that are directed at FI have led to one PC in the analysis. Based on the discriminant scores, the countries were classified as low-level and high-level FI countries [20]. Similarly, for this analysis, the loading of the first component could be used to identify the behavior of the FI in South Asian countries, and further established an upward positive trend of FI for each of the South Asian countries throughout the 15 years.…”
Section: Pretest Analysis Resultsmentioning
confidence: 99%
“…Five variables that are directed at FI have led to one PC in the analysis. Based on the discriminant scores, the countries were classified as low-level and high-level FI countries [20]. Similarly, for this analysis, the loading of the first component could be used to identify the behavior of the FI in South Asian countries, and further established an upward positive trend of FI for each of the South Asian countries throughout the 15 years.…”
Section: Pretest Analysis Resultsmentioning
confidence: 99%
“…Many researchers focused on the measuring the status of financial inclusion, namely measuring financial inclusion index (Sarma, 2008; Adalessossi and Kaya, 2015; Allen et al, 2012, etc.) [5,6,14]. However, accurate measurement of the status financial inclusion is only the first step of studying financial inclusion, and the next step is how to achieve the effective development of financial inclusion and make it sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…Cámara and Tuesta (2014) relied on demand and supply-side information to measure the extent of financial inclusion at country level for eighty-two developed and less-developed countries [20]. With Global Findex Database, Adalessossi and Kaya (2015) measured the degree of financial inclusion in the African countries [6]. They found out of the 41 total countries 27 had a low level in financial inclusion whereas 14 had a high level.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, Camara and Tuesta (2014) studied 82 countries (both developed and less developed) and relied on the information of demand and supply. Fifth, Adalessossi and Kaya (2015) calculated the financial inclusion index of African countries with the help of the Global Findex database, and they reported that 27 African countries have lower financial inclusion and only 14 African countries have greater financial inclusion out of total 41 countries. Sixth, Ambarkhane et al (2016) measured the financial inclusion index through non-banking financial companies and picked the insurance companies’ pensions plan.…”
Section: Literature Reviewmentioning
confidence: 99%